Highly Efficient Sensorless Multicontrol Mode Compressor IPMSM Drive With Seamless Transitions - Dianov, Anton (IEEE transactions on power electronics, 2022)
Motor drives with interior permanent magnet synchronous motors are typically used with vector or rectangular control (RC). Both of these control methods have well-known pros and cons; therefore, the most appropriate control mode is selected at the stage of drive design. Then, at the experimental verification of the drive prototype, the optimal pulse-width modulation (PWM) frequency is detected and the operation of motor drive is adjusted to this frequency and the corresponding sampling time. The systems constructed according to this algorithm have efficiency with one peak, which is typically selected to be at the rated mode motor drive. As a result, motor drives operate in other modes with lower efficiency, which is subject to further improvements. This article proposes the usage of multicontrol mode, which combines the benefits from each control method. The author suggests usage of the RC at lower speeds and vector control at higher speeds. Furthermore, the PWM frequency of motor drives is also changed, depending on the operating speed, which improves drive performance. This combination of control methods results in efficiency, which has several maximums and increases overall drive efficiency.